COVID-19 Outcomes Among Solid Organ Transplant Recipients: A Case-control Study. Issue 1 (January 2021) - Sharma, Pratima; Chen, Vincent; Fung, Christopher M.; Troost, Jonathan P.; Patel, Vaiibhav N.; Combs, Michael; Norman, Silas; Garg, Puneet; Colvin, Monica; Aaronson, Keith; Sonnenday, Christopher J.; Golob, Jonathan L.; et al.
Abstract : Background: Solid organ transplant (SOT) recipients are considered to be "vulnerable" to COVID-19 infection due to immunosuppression. To date, there are no studies that compared the disease severity of COVID-19 in SOT recipients with nontransplant patients. Methods: In this case-control study, we compared the outcomes of COVID-19 between SOT recipients and their matched nontransplant controls. The cases were all adult SOT recipients (N = 41) from our academic health center who were diagnosed with COVID-19 between March 10, 2020 and May 15, 2020 using positive reverse transcriptase polymerase chain reaction for SARS-CoV2. The controls (N = 121) were matched on age (±5 y), race, and admission status (hospital or outpatient). The primary outcome was death and secondary outcomes were severe disease, intubation and renal replacement therapy (RRT). Results: Median age of SOT recipients (9 heart, 3 lung, 16 kidney, 8 liver, and 5 dual organ) was 60 y, 80% were male and 67% were Black. Severe disease adjusted risk of death was similar in both the groups (hazard ratio = 0.84 [0.32–2.20]). Severity of COVID-19 and intubation were similar, but the RRT use was higher in SOT (odds ratio = 5.32 [1.26, 22.42]) compared to non-SOT COVID-19 patients. Among SOT recipients, COVID-19-related treatment with hydroxychloroquine (HCQ) was associated with 10-fold higher hazard of death compared to without HCQ (hazard ratio = 10.62 [1.24–91.09]). Conclusions: Although African Americans constituted one-tenth of all SOT in our center, they represented two-thirds of COVID-19 cases. Despite high RRT use in SOT recipients, the severe disease and short-term death were similar in both groups. HCQ for the treatment of COVID-19 among SOT recipients was associated with high mortality and therefore, its role as a treatment modality requires further scrutiny. Abstract : Supplemental Digital Content is available in the text.